2002
DOI: 10.1103/physrevlett.88.033902
|View full text |Cite
|
Sign up to set email alerts
|

High-Brightness High-Order Harmonic Generation by Truncated Bessel Beams in the Sub-10-fs Regime

Abstract: Low-divergence, high-brightness harmonic emission has been generated by using a fundamental beam with a truncated Bessel intensity profile. Such a beam is directly obtained by using the hollow-fiber compression technique, which indeed allows one to optimize both temporal and spatial characteristics of the high-order harmonic generation process. This is particularly important for the applications of radiation, where extreme temporal resolution and high brightness are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 21 publications
5
47
0
Order By: Relevance
“…Thus for TB beams a broad good phase-matching region close to the axis from z=-1.5 to 1.5 mm for "short"-trajectory harmonics can be achieved. This conclusion is consistent with the experimental results of Nisoli et al [141]. For the typical gas-jet length (∼ 1 mm), the phase matching conditions should depend strongly on the position of the gas jet, and for whether it is Type-1 Bessel or Gaussian (w 0 =25 µm) beams.…”
Section: Phase Matching Conditions At the Low Gas Pressuresupporting
confidence: 81%
See 3 more Smart Citations
“…Thus for TB beams a broad good phase-matching region close to the axis from z=-1.5 to 1.5 mm for "short"-trajectory harmonics can be achieved. This conclusion is consistent with the experimental results of Nisoli et al [141]. For the typical gas-jet length (∼ 1 mm), the phase matching conditions should depend strongly on the position of the gas jet, and for whether it is Type-1 Bessel or Gaussian (w 0 =25 µm) beams.…”
Section: Phase Matching Conditions At the Low Gas Pressuresupporting
confidence: 81%
“…Nisoli et al [141] have shown that the characteristics of HHG using a truncated Bessel As discussed in Sec. 1.3.1, phase matching is a pre-requisite for efficient generation of high harmonics.…”
Section: Phase Matching Conditions At the Low Gas Pressurementioning
confidence: 99%
See 2 more Smart Citations
“…This angle was found by scanning over different angle values although in an experiment it would be easier to scan over the gas pressure. We found an optimal cone angle of 0.44 deg: whilst the technology to generate a SLP is still to be developed, a 5-7 fs PBB may be readily obtained by generating the harmonics in an appropriate hollow-core fibre [38]. Indeed, the modes of these fibres are precisely PBBs and the fundamental-mode cone angle is related to the fibre diameter d by d = 2.4048 · (2c)/ω 0 sin θ 0 .…”
mentioning
confidence: 99%